PTH-042 Colorectal stenting as a bridge to surgery: a decade of single centre success. (8th June 2018) - Steward, Lindsay; Manook, Miriam; Stafford, Waveney; Taylor, Fiona; Andreani, Stefano; Watson, Alan
Abstract : Introduction: Colonic stenting in obstructing left sided colorectal cancer (CRC) using self-expanding metallic stents has been utilised as a conservative management intervention, as well as a bridge to definitive surgery. Despite high reported success rates technically and clinically of stent deployment, as well as improved rates of primary anastomosis, controversy remains about the use of this procedure as a bridge to surgery. We report on a decade of single centre experience. Methods: Retrospective analysis of patients requiring urgent colorectal cancer stenting as a bridge to surgery between 2006 and 2017. Primary outcomes measured were clinical and technical success. Secondary outcomes recorded were survival, complications, primary anastomosis and stoma formation Results: 36 patients underwent CRC stenting with the intention of being a bridge to elective surgery, of whom 44% were female. Mean age was 65.7 years. The majority of cases (84%) were undertaken by one of the 3 main operators. At staging, 9 patients (25%) were T3; 17 (47.3%) T4. 25% of patients were ASA 3. Technical success was reported in 89% of cases and clinical success 86%. At elective surgery primary anastomosis was achieved in 61%. 5 reported early complications, including 2 clinical perforations and 2 radiological perforations. Mean survival post stenting procedure was 24 months (range 3–55 months), with death due to metastatic CRC. There were no deaths within 30 days. Conclusions: We demonstrate excellent technical success with this treatment modality. By temporising patients using endoscopic stenting, patients are optimised for elective surgery by colorectal surgeons with good primary anastomosis rates, and excellent post procedure mortality.